Long-term results of electrothermal shrinkage of wrist ligaments followed by sensorimotor training (Norway): A cohort study - Ildiko Marta Tanczos Rigone; Istvan Zoltan Rigo; Tone Vaksvik (Fysioterapeuten, 2023)
Aim: To examine the short- and long- term results of electrothermal shrinkage followed by sensorimotor training for patients with wrist pain after injury to the scapholunate (SL) and lunotriquetral (LT) ligament.